Increasing Vocabulary Mastery Through Vocabulary Race Game at MTs Husnul Khatimah - Izzatur Rifda; Arso Setyaji; Tarcisia Sri Suwarti (Universitas PGRI Madiun, 2025)
Vocabulary mastery is crucial for successful language learning. This study examines the effect of the Vocabulary Race Game on the vocabulary mastery of seventh-grade students at MTs Husnul Khatimah, Tembalang. Using a quantitative quasi-experimental design, two classes (46 students) were assigned as experimental and control groups. The Vocabulary Race Game was applied only in the experimental class, while the control class received traditional instruction. Data were collected through pretests and posttests and analyzed using an independent samples t-test. The experimental class improved from a mean pretest score of 50.54 to 64.89 on the posttest, while the control class increased from 37.50 to 45.54. The t-test yielded a significant p-value of 0.000016, indicating that the Vocabulary Race Game effectively enhanced students vocabulary mastery. The findings highlight the importance of incorporating interactive and game-based strategies to increase student engagement in vocabulary learning. Moreover, this study provides empirical evidence supporting the use of competitive learning activities in English language classrooms. Thus, this method can serve as an engaging and effective alternative to traditional teaching.